The Learning Management of Project Based Learning along with Questioning Based on Sufficiency Economy Philosophy to Enhance Project Proceeding Ability and Thinking - Practicing Process for Secondary 3 (Grade 9) Students - Pongnarin Maowtub, Saiphin Siharak (International Journal of Advanced Science and Technology, 2020)
King Bhumibol Adulyadej is known around the world. In terms of the philosophy of sufficiency economy. And many countries have adopted the philosophy of this sufficiency economy in life. So the purposes of this research were: 1) to compare the project proceeding ability of students between who are learning by using project based learning with questions based on the sufficiency economy philosophy and the students who received the learning by the traditional method and 2) to compare the thinking – practicing process based on the sufficiency economy philosophy of students between who are learning by using project based learning with questions based on the sufficiency economy philosophy and students who have been learning by the traditional method. The samples used in the study were grade 9 students at Suankularb Wittayalai Rangsit School, 2nd semester, academic year 2019, consisting of 2 classrooms that were selected by Group Random sampling. The research instruments consisted of a plan of learning activities by using project-based learning together with questions based on the sufficiency economy philosophy and plan to organize learning activities in the traditional method, project proceeding record form, project ability assessment form, form for recording self-directed questions based on the sufficiency economy philosophy and the form for assess thinking – practicing process compliance with the philosophy of the sufficiency economy. Method research used statistics for data analysis were the mean, standard deviation and t-test. The results showed that: 1) project proceeding ability scores of students who received by using project-based learning together with questions based on sufficiency economy philosophy after studying were higher than those received by traditional methods with statistical significance at 05 level, and 2) thinking – practicing by project based learning process scores were higher than the students who received the learning management in the traditional method.